(untitled) (Research, Society and Development, 2021)
Bees have complex symbiotic interactions with microorganisms, which, in exchange for shelter and food, provide their hosts with several benefits, such as food metabolism, detoxification, supply of essential nutrients, protection against invasive species and pathogens, modulation of development and immunity. Thus, these symbiotic relationships are often essential for the bees’ survival. The aim of this study is to present the role of the bacterial intestinal microbiota of eusocial bees and the importance it plays in its host. We also highlight what these bacteria are and how they are acquired. The databases of PubMed, CAPES Journals and Academic Research Tool (Scholar Google) were used, in a period of time from 2009 to 2020, related to the role of the intestinal microbiota of eusocial bees. Altogether 28 articles were found, the data obtained were tabulated exposing the host species and the benefits that the bacterial microbiota exerts. In addition, the main activities performed by these intestinal symbionts were selected and each one was discussed, explaining, based on related studies, how they work.